2015
DOI: 10.1111/jth.12788
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in hemostasis

Abstract: To cite this article: Teruel-Montoya R, Rosendaal FR, Mart ınez C. MicroRNAs in hemostasis. J Thromb Haemost 2015; 13: 170-81.Summary. Epidemiologic studies have revealed that modification of the levels of individual components of the hemostatic system may have effects on the development of thrombosis or hemorrhage. To maintain the necessary equilibrium, the hemostatic system is finely regulated. It is known that acquired factors and/or alterations in genes (single-nucleotide polymorphisms or mutations) may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 99 publications
(107 reference statements)
1
41
0
Order By: Relevance
“…Since these two modules contain over 100 genes each, we took advantage of the putative role of miRNAs in platelet reactivity regulation (Teruel-Montoya et al 2015) to identify the most promising genes by selecting candidate miRNAs' targets within these modules. The miRNA expression levels correlated well with previous studies (Landry et al 2009;Nagalla et al 2011;Simon et al 2014) and 12 miRNAs were differentially expressed between the two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these two modules contain over 100 genes each, we took advantage of the putative role of miRNAs in platelet reactivity regulation (Teruel-Montoya et al 2015) to identify the most promising genes by selecting candidate miRNAs' targets within these modules. The miRNA expression levels correlated well with previous studies (Landry et al 2009;Nagalla et al 2011;Simon et al 2014) and 12 miRNAs were differentially expressed between the two groups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two sub-networks were thus identified containing 123 and 182 genes, respectively. Since miRNAs seem to play an important role in platelet physiology (Esteller 2011;Teruel-Montoya et al 2015;Willeit et al 2013), we evaluated differentially expressed platelet miRNAs in these 2 groups of patients and identified their predicted gene targets within the subnetworks. We provide here original findings derived from an integrative networkbased approach for the understanding of the modulators of platelet reactivity in CV patients.…”
mentioning
confidence: 99%
“…This makes it likely that this phenotype is caused by the genetic defect found in these families. Despite the absence of linkage data, other potential causes for antithrombin deficiency in these patients may be found outside the direct molecular context of SERPINC1 gene regulation, such as microRNAs (Teruel‐Montoya et al , ) or the antithrombin‐modulating gene LARGE1 (de la Morena‐Barrio et al , ). Recently, de la Morena‐Barrio et al () identified hypoglycosylation, not only of antithrombin but also of other N‐glycoproteins in 8 out of 30 antithrombin‐deficient cases without alterations in SERPINC1 .…”
Section: Discussionmentioning
confidence: 99%
“…This makes it likely that this phenotype is caused by the genetic defect found in these families. Despite the absence of linkage data, other potential causes for antithrombin deficiency in these patients may be found outside the direct molecular context of SER-PINC1 gene regulation, such as microRNAs (Teruel-Montoya et al, 2015) or the antithrombin-modulating gene LARGE1 The novel mutations included 3 missense mutations, 1 splice site variant and 1 insertion. The novel missense mutation p.Phe179Cys (147) was identified in 1 family (Family A).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are small non-coding conserved RNAs of about 22 nucleotides, which predominantly bind to the 3 0 untranslated region (UTR) of target genes (Bartel, 2009). Recent in vitro studies demonstrated that plasminogen-activator inhibitor-1 (PAI-1), fibrinogen, tissue factor and factor XI may be regulated by miRNAs, thereby supporting their role in regulating levels of haemostatic factors (Fort et al, 2010;Teruel et al, 2011;Marchand et al, 2012;Salloum-Asfar et al, 2014;Teruel-Montoya et al, 2015). Recent in vitro studies demonstrated that plasminogen-activator inhibitor-1 (PAI-1), fibrinogen, tissue factor and factor XI may be regulated by miRNAs, thereby supporting their role in regulating levels of haemostatic factors (Fort et al, 2010;Teruel et al, 2011;Marchand et al, 2012;Salloum-Asfar et al, 2014;Teruel-Montoya et al, 2015).…”
Section: Discussionmentioning
confidence: 99%